2021
DOI: 10.1080/1331677x.2021.1985577
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the nexus between CO 2 emissions, economic growth, energy consumption and pilgrimage tourism in Saudi Arabia

Abstract: Every year millions of Muslims go to Saudi Arabia to fulfil pilgrimage worship, thus Saudi Arabia is such a religious centre brings with it various consequences. In this context, this paper investigates the nexus between CO2 emissions, economic growth, energy consumption and pilgrimage tourism in Saudi Arabia for the period of 1968-2017. The dynamic ordinary least squares (DOLS) and fully-modified ordinary least squares (FMOLS) methods are employed in this study. FMOLS results prove that energy consumption, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 61 publications
(75 reference statements)
2
26
0
Order By: Relevance
“…Moreover, some studies (such as Weimin et al 2021;Hussain and Rehman 2021;Chishti et al 2021) have found a negative relationship between renewable energy consumption and environmental pollution levels and concluded that renewable energy consumption improves environmental quality. They also discovered a positive and significant relation between FDI and CO 2 emissions, while in the case of PIC nations (Pakistan, India, and China), Ozturk et al (2021a, b) estimated that energy structure raises CO 2 emissions, but energy intensity can lower CO 2 emissions. Various researchers found a positive relationship between energy usage and pollution levels and concluded that increased energy usage have an adverse impact on carbon emissions (Rehman et al 2021a, b, c;Ozturk et al 2021a, b;Murshed et al 2021;Ahmad et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some studies (such as Weimin et al 2021;Hussain and Rehman 2021;Chishti et al 2021) have found a negative relationship between renewable energy consumption and environmental pollution levels and concluded that renewable energy consumption improves environmental quality. They also discovered a positive and significant relation between FDI and CO 2 emissions, while in the case of PIC nations (Pakistan, India, and China), Ozturk et al (2021a, b) estimated that energy structure raises CO 2 emissions, but energy intensity can lower CO 2 emissions. Various researchers found a positive relationship between energy usage and pollution levels and concluded that increased energy usage have an adverse impact on carbon emissions (Rehman et al 2021a, b, c;Ozturk et al 2021a, b;Murshed et al 2021;Ahmad et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They also discovered a positive and significant relation between FDI and CO 2 emissions, while in the case of PIC nations (Pakistan, India, and China), Ozturk et al (2021a, b) estimated that energy structure raises CO 2 emissions, but energy intensity can lower CO 2 emissions. Various researchers found a positive relationship between energy usage and pollution levels and concluded that increased energy usage have an adverse impact on carbon emissions (Rehman et al 2021a, b, c;Ozturk et al 2021a, b;Murshed et al 2021;Ahmad et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of economic growth and environmental sustainability has been persisting over the years and has called for the adoption of holistic strategies such as technological innovation to ensure sustainable development (Awawdeh et al 2022;Kraus et al 2020;Ozturk et al 2022). Examples of such innovation are Fintech and GF, both of which have gained popularity, particularly in the wake of the epidemic (Xie et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A remarkable part of academic literature has investigated various features of the effect of civil aviation on environmental pollution. In this sense, recent academic research regarding the relationship between air transport, economic growth, and environmental pollution (Eğilmez, 2020;Erdogan et al, 2020;Gyamfi et al, 2022;Kalayci and Özden, 2021;Kalayci and Yazici 2016;Ozkan et al, 2019;Ozturk et al, 2021;Sohail et al, 2021;Yazici, 2022) have suggested that reducing the existence of dirtiness is so vital in terms of protecting the environment which is mostly depend on the government policies and economic sanctions. Altuntaş and Kılıç (2021) investigate the relationship between total airline passenger, freight traffic and Gross Domestic Product (GDP) for Turkey by implementing ARDL and Toda Yamamoto methods.…”
Section: Literature Reviewmentioning
confidence: 99%